Out of Africa: What drives the Pressure to emigrate? - Hendrik P. van Dalen; George Groenewold; Jeanette J. Schoorl (Tinbergen Institute, 2003)
This paper evaluates the strength of social and economic forces that affect the pressure to emigrate 'out of Africa' for four distinctly different African countries (Morocco, Egypt, Senegal and Ghana). In general, great expectations about attaining a higher living standard and expected low job search costs abroad are strong forces that drive emigration intentions out of Africa, especially in Ghana and Senegal. Signs of positive selection with respect to the level of education of potential migrants are only present in Ghana and Egypt. The differences in intentions by age and sex are also quite noteworthy, although the influence of sex differs quite distinctly across countries. Return migrants are on average more set to emigrating judging from their stated intentions although there are signs of negative selection within the group of return migrants in Ghana and Egypt. The network effects of potential migrants turn out to be less important than one might expect from actual migration behaviour. Both ties within the household with household members who have international migration experience and ties with current migrants affect intentions only in Ghana and Egypt and it affects the intentions of women far stronger than that of men. The implication of these findings is that due to the slow growth prospects of these African countries the pressure to emigrate 'out of Africa' can be a long lasting phenomenon.
Keywords: F22; O52; P2; 330; migration; intentions; Africa; social networks.; Auswanderung; Marokko; Ägypten; Senegal; Ghana; Afrika; Soziales Netzwerk